The Improving the Professional Competence of High School Teachers in Yogyakarta Through the Development of Classroom Action Research Management (PTK) Based on Android Mobile Applications - Danu Eko Agustinova; Nur Lailly Tri Wulansari; Kurnia Nur Fitriana (CV. Media Digital Publikasi Indonesia, 2025)
The need and skills to write scientific papers through classroom action research are a must for every educator. Classroom action research is part of evaluating a series of learning processes and continuous professional development (PKB) by the law mandate. This study aims to develop an integrated service system for classroom action research based on Android mobile applications to facilitate educators in developing professionalism competencies on an ongoing basis. This research uses the research and development method with the 4D development model, which includes (1) Define, (2) Design, (3) Development, and (4) Disseminate. The advantages of the products developed in this study are (1) open access, (2) adoption of the latest digital platform-based information technology innovations, (3) improving digital literacy, (4) building Penta helix collaboration between government, private, community, non-governmental organizations, universities, and mass media, (5) easy to apply and economical in access, (6) encouraging unlimited creativity, (7) using sustainable materials, (8) developing application-based PTK training management and encouraging the improvement of professional competence of high school teachers in Yogyakarta.